(untitled) (De Signos y Sentidos, 2018)
Between 1955 and 1958, during the intervention of the national government to the Universidad Nacional del Litoral, a sistematic process of elimination of contents, ideas and symbols from the Peronist period (called in Spanish «desperonización») involved a set of actions. Professors who had links with the Peronist regime were removed or resigned their positions. Those whose university careers were interrupted in 1946 were reincorporated. In addition, institutional restructuring was initiated to erase allegorical symbols of Peronism. This article, precisely, addresses a dimension of this process by analyzing the discourse of the intervening authorities. The authorities’ interpretation about this critical juncture appealed to reformism in order to achieve the elimination of Peronism from the university.